2011
DOI: 10.1111/j.1364-3703.2011.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polymorphism and transcription of the effector gene Avr1b in Phytophthora sojae isolates from China virulent to Rps1b

Abstract: The effector gene Avr1b-1 of Phytophthora sojae determines the efficacy of the resistance gene Rps1b in soybean. The sequences of the Avr1b-1 locus in 34 Chinese isolates of P. sojae were obtained and analysed by polymerase chain reaction (PCR) and inverse PCR. Four different alleles and a complete deletion mutation of the Avr1b-1 gene were identified. Molecular analysis of the deletion breakpoints in the Avr1b-1 locus revealed that an 8-kb DNA sequence containing Avr1b-1 was deleted and a 12.7-kb DNA sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Transcriptional silencing of effector genes is one of the mechanisms that plant pathogenic oomycetes deploy to avoid the activation of host R -gene-mediated immunity. A few examples have been described for races of P. infestans and P. sojae in which the expression of specific RXLR effectors is correlated with their virulence or avirulence on specific host genotypes [29,55-59]. In P. sojae , these transcriptional polymorphisms have been attributed to insertions or deletions in the promoter region [55,57,59].…”
Section: Effector Gene Expressionmentioning
confidence: 99%
“…Transcriptional silencing of effector genes is one of the mechanisms that plant pathogenic oomycetes deploy to avoid the activation of host R -gene-mediated immunity. A few examples have been described for races of P. infestans and P. sojae in which the expression of specific RXLR effectors is correlated with their virulence or avirulence on specific host genotypes [29,55-59]. In P. sojae , these transcriptional polymorphisms have been attributed to insertions or deletions in the promoter region [55,57,59].…”
Section: Effector Gene Expressionmentioning
confidence: 99%
“…Many Avr effectors escape recognition by cognate Rps genes in P. sojae by deletion, such as Avr1a, Avr1b, Avr1c and Avr1d (Qutob et al 2009;Cui et al 2012;Na et al 2013;Na et al 2014;Arsenault-Labrecque et al 2018). In three isolates, Avr1c was deleted in an 8.8 kb or 10.8 kb region containing two copies of Avr1a, one copy of Avr1c, and one copy of Avh72 (Na et al 2014;Arsenault-Labrecque et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Point mutations and loss of transcript of Avr1b-1 induced virulence (Shan et al 2004). In addition, the transposable elements insertion resulted in deletion of Avr1b-1 from Chinese isolates (Cui et al 2012). Avr1d is present in P. sojae strains avirulent to Rps1d, but is absent from the genome of virulent strains (Na et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown how the primary sequences of host‐translocated effectors have been shaped by positive selection, and how genes undergo accelerated birth and death evolution (Cui et al ., ; Stassen and Van den Ackerveken, ; Win et al ., ). In this study, sequence polymorphism was not observed for SCR96.…”
Section: Discussionmentioning
confidence: 99%